Sharia Compliance Indicators and Implications for Fraud Risk in Sharia Commercial Banks in Indonesia - nasfi, nasfi; Prawira, Adi; Lutfi, Ahmad; Suhatman, Suhatman; Sabri, Sabri (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
Every bank operating, including Islamic commercial banks, has the potential to experience the risk of fraud. Fraud cases that occurred in Islamic Commercial Banks from 2022 to 2024. This study aims to analyze the influence of Sharia compliance indicators, measured by the Islamic Income Ratio (IIR), Profit Sharing Ratio (PSR), Islamic Investment Ratio (IsIVR), and Zakat Performance Ratio (ZPR), on fraud. Secondary data sources were taken from the Financial Services Authority (OJK) website, where 14 Sharia Commercial Banks submitted complete financial reports to the OJK for a three-year period. This resulted in a sample of 40 selected using a purposive sampling method. The analysis was conducted using panel data regression with Eviews 12. The results showed that IsIVR had a positive effect on fraud, while IIR, PSR, and ZPR did not have a significant effect. Simultaneously, all independent variables had a positive and significant effect on fraud in Sharia Commercial Banks